Comparison Of Consumptive Behavior Among Students - Oki Khairul Hikmah (Sekolah Tinggi Agama Islam Kuningan, 2022)
Backgrounds: The influence of student consumptive behavior is influenced by several factors, both internal and external. The purpose of this study was to compare the effects of spending, lifestyle, and self-control on the consumptive behavior of students between faculties at IAIN Syekh Nurjati Cirebon. Aim: The subjects of this study were students of the Faculty of Tarbiyah and Teacher Training (FITK) and the Faculty of Sharia and Islamic Economics (FSEI). The population in this study found 8049 students. Methods: The number of samples in this study were 381 students calculated by the Slovin formula with an error rate of 5%. The data analysis method used is the independent t-test analysis method. Findings: The results of the study showed that the calculation of the Comparative Test obtained, lifestyle differences were significant between FITK and FSEI students. Where the average value of competition among FSEI students is higher than the average value of FITK students. Meanwhile, there is no significant difference between FITK and FSEI in the Comparative Test of self-control and monthly expenses